The Effect of Viral Marketing “Oreo X Blackpink” On Oreo Customer Loyalty (Survey on Instagram Followers @oreo_indonesia) - Hartadi, Nabeel Putra; Ardia, Velda (PT Literasi Nusantara Publisher, 2023)
Viral Marketing is the digital version of Word of Mouth marketing, involving the creation of videos, advertisements and other marketing content that is so infectious that customers will search for it or share it with friends. Oreo is a product that implements viral marketing activities by collaborating with Blackpink. The purpose of this study was to determine the influence of